S77C-ΔC7-CueR a 199mHg PAC study of the protein metal site structure - Balogh Ria Katalin; Jancsó Attila; Gyurcsik Béla; Schell J.; Correia J. G.; Thulstrup P. W.; Hemmingsen L. (2024)
The CueR protein regulates the cytosolic concentration of Cu(I) in bacteria such as E. coli. With this work we aimed to remodel the linear two-coordinate metal site with Cys112 and Cys120 as ligands in CueR to a tricoordinate site similar to that observed in the Hg(II) sensor protein MerR. This was done by introducing an additional cysteine near the metal site in the modified S77C-ΔC7-CueR variant, inspired by the fact that Ser77 in CueR is replaced by a cysteine in MerR. 199m Hg PAC spectroscopic data indicate that two NQIs are present at pH 8.0, most likely reflecting HgS 2 and HgS 3 coordination modes, and demonstrating that the design of a pure HgS 3 metal site was not achieved. Lowering the pH to 6.0 or the temperature to −196 °C had surprisingly similar effects, giving rise to highly distorted trigonal Hg(II) coordination. Tentatively, this might reflect that the histidine just next to Cys77 (His76) coordinates forming a HgS 2 N metal site structure. Further redesign beyond the first coordination sphere appears to be required to efficiently stabilize the HgS 3 metal site structure at physiological pH.
Keywords: Kémiai tudományok